IMPORTANCE OF 6-MINUTE WALK TEST IN DIAGNOSTICS OF RARE METABOLIC MYOPATHY - A CASE REPORT OF CARNITINE PALMITOYLTRANSFERASE II DEFICIENCY - Angelkova Natalija; Shukarova Angelovska, Elena; Kocova Mirjana; Duma, Filip; Sabolich Vesna; Mandjukovska Hristina (Институт за јавно здравје на Република Македонија = Institute of public health of Republic of Macedonia, 2017)
Diagnosis of rare inherited neuromuscular disorders is sometimes delayed due to variations in time of onset, different clinical appearance and limited diagnostic possibilities. The management of patients starts with neurological examination, followed by specific laboratory tests and neurophysiologic assessment. In the era of molecular medicine, molecular biology tools are useful in avoiding some of the invasive investigations such as muscle biopsy. We present a boy with a mild form of metabolic myopathy due to carnitine palmitoyltransferase 2 deficiency diagnosed upon timed functional assessment. A child had delayed developmental milestones, associated with fatigue and muscle pain during exercising and longer walks. There were no episodes of myoglobinuiria during exercise or during febrile illnesses. Neurological examination reveled proximal muscle weakness. Serum creatine kinase (CK) and serum lactate were above normal limits. Serum acylcarnitine profile was normal. Short timed functional tests such as 10 meters walk/run test showed normal results. Nord Star Ambulatory Assessment showed difficulties in balance and jumping. Diagnosis of myopathy was suspected after performance of 6-minute walk test, when the passed distance was 327 meters with slowing and fatigue. EMG and echocardiography were within normal range. Diagnosis was established by sequencing of the CPT II gene which revealed c.338C>T (p.Ser113Leu) mutation in homozygous form as characteristic CPT II deficiency profile.
ВАЖНОСТ НА 6-МИНУТНИОТ ТЕСТ НА ОДЕЊЕ ВО ДИЈАГНОСТИКА НА РЕТКА МЕТАБОЛИЧКА МИОПАТИЈА – ПРИКАЗ НА СЛУЧАЈ НА КАРНИТИН ПАЛМИТОИЛ ТРАНСФЕРАЗА 2 ДЕФИЦИТ
Keywords: 6 minutes walking test; carnitine palmitoyltransferase II deficiency